2011
DOI: 10.4049/jimmunol.1003318
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 Overexpression Shifts Lympho- and Myelopoiesis by Dysregulating Site 2/Site 3 Cleavage Products of Notch

Abstract: Although the physiological consequences of Notch signaling in hematopoiesis have been extensively studied, the differential effects of individual notch cleavage products remain to be elucidated. Given that ADAM10 is a critical regulator of Notch and that its deletion is embryonically lethal, we generated mice that overexpress ADAM10 (ADAM10 transgenic [A10Tg]) at early stages of lympho- and myeloid development. Transgene expression resulted in abrogated B cell development, delayed T cell development in the thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 45 publications
0
51
0
Order By: Relevance
“…During lymphoid-and myeloid-development, the Notch-signaling pathway needs to be tightly regulated to control cell-fate-and lineage-decision events. Increasing the expression of ADAM10 during early stages of hematopoiesis abrogated B-cell development, delayed T-cell development and led to a systemic expansion of myeloidderived suppressor cells (Gibb et al 2011). Conversely, the usage of a specific ADAM10 inhibitor in a coculture model of hematopoietic stem cells (HSCs) and bone marrow stromal cells (BMSCs) showed the expansion of B-lymphocytes.…”
Section: Alpha Secretase and Ectodomain Sheddingmentioning
confidence: 98%
See 1 more Smart Citation
“…During lymphoid-and myeloid-development, the Notch-signaling pathway needs to be tightly regulated to control cell-fate-and lineage-decision events. Increasing the expression of ADAM10 during early stages of hematopoiesis abrogated B-cell development, delayed T-cell development and led to a systemic expansion of myeloidderived suppressor cells (Gibb et al 2011). Conversely, the usage of a specific ADAM10 inhibitor in a coculture model of hematopoietic stem cells (HSCs) and bone marrow stromal cells (BMSCs) showed the expansion of B-lymphocytes.…”
Section: Alpha Secretase and Ectodomain Sheddingmentioning
confidence: 98%
“…Conversely, the usage of a specific ADAM10 inhibitor in a coculture model of hematopoietic stem cells (HSCs) and bone marrow stromal cells (BMSCs) showed the expansion of B-lymphocytes. These observations suggest that ADAM10 plays an essential role for Notch-mediated cell-fate decisions during hematopoiesis and could therefore serve as a potential target for hematological disorders (Gibb et al 2011).…”
Section: Alpha Secretase and Ectodomain Sheddingmentioning
confidence: 99%
“…The cell-intrinsic expansion of Gr-1 + CD11b + cells in the ADAM10 over-expression transgenic mice was related to the accumulation of the S2 product and was also accompanied by mild defective T cell development and abrogated B cell development [98]. In comparison, both cell-autonomous and non-hematopoietic components were identified to contribute to the aberrant expansion of myeloid compartment in ADAM10-deficient mice [99].…”
Section: Myeloproliferation In Other Mouse Models Of Dysregulated Notmentioning
confidence: 97%
“…Not surprisingly, not only does the loss of function of S3 cleavage enzyme complex cause myeloproliferation, but also number of defective Notch S2 cleavage, either through over-expression [98] or conditional inactivation of AD-AM10 [99], leading to a myeloid hyperplasia phenotype. The cell-intrinsic expansion of Gr-1 + CD11b + cells in the ADAM10 over-expression transgenic mice was related to the accumulation of the S2 product and was also accompanied by mild defective T cell development and abrogated B cell development [98].…”
Section: Myeloproliferation In Other Mouse Models Of Dysregulated Notmentioning
confidence: 98%
“…Overexpression of ADAM10 in early lymphoid and myeloid development resulted in abrogated B cell development and dysregulated myelopoiesis. In vitro experiments with hematopoietic cells revealed that overexpression of ADAM10 increases the proteolysis of Notch receptors and thereby shifts lympho-and myelopoiesis (51). B cell-specific ADAM10 deficiency in mice (driven by CD19-Cre) prevented marginal zone B cell development, which is dependent on Notch2 signaling (50).…”
Section: Adam10mentioning
confidence: 99%